Apuntes sobre la trayectoria del tabaco en el cantón de Palmares - Alfaro, Alicia (2013)
The following article has as its main objective to analyze the historical tobacco’s route in Palmares, Alajuela ́s canton, since the thirtieth decade of the XIX century (date in which the cultivation began in this town), to the 1960 decade (time in which the Tobacco Cooperatives declined). In this sense, general aspects of tobacco ́s history in Costa Rica are mentioned; moreover, the specialty of this bean in the community is incorporated too, making emphasis in the cooperative development growth, due to its cultivation, processing and commercialization.